Pelatihan Pemanfaatan Media Digital Quizizz sebagai Media Pembelajaran Interaktif Bagi Guru SD - Gagaramusu, Yusdin; Zulnuraini; Shalehuddin; Abdullah Joni Guci, Ammar; Indriastuti Purnamasari , Danti (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The development of digital technology has driven the need for learning innovation, including for elementary school teachers who are required to create an interactive learning environment. Training on the use of the digital media Quizizz at SDN Inpres Perumnas aims to improve teachers' skills in integrating technology into the teaching and learning process. Teachers are expected to master the practical use of the application while understanding learning strategies to encourage student motivation and engagement. The activity was carried out in five stages: preparation in the form of coordination and preparation of materials, counseling on the importance of interactive digital media, hands-on training from account creation to question preparation, mentoring in classroom implementation, and demonstrations of learning with students. Evaluation was carried out through pretests, posttests, and practical observations. The results showed that teachers were able to follow all stages well. The average pretest score was only 45%, indicating teachers' limited understanding of Quizizz. After the training, the average posttest score increased to 85%. The highest increase occurred in understanding the superior features (from 30% to 90%) and the advantages of Quizizz compared to conventional quizzes (from 35% to 88%). Basic understanding of the purpose of use also increased from 40% to 90%. The primary benefit of this activity was increased teacher readiness to design interactive learning and broadened knowledge about the use of digital media for evaluation. The conclusion of this activity confirmed that the Quizizz training not only strengthened teacher competency but also opened up opportunities for school community involvement in supporting technology-based learning transformation